The effects of ginger and black seed extracts on albino rat spermatogenesis induced with hyperuricemia - Hussein, Ridha Hassan (Sulaimani Journal for Pure and Applied Sciences, 2021)
Both ginger and black seed are promising nutraceutical natural plant products with reported diverse therapeutic properties. However, there is limited research on their effects on spermatogenesis in animals, especially rats. Thus, the current manuscript investigates the role of ginger and black seed on male albino rats regarding testicular function and spermatogenesis capacity. For this purpose, 24 animals were divided into 6 groups; each group was induced experimentally with hyperuricemia using intraperitoneal injections of oxonic acid for 1 week, except the first group that was used as a negative control group and received intraperitoneal injection of 0.9% saline solution without any further treatment. Then, the second group acted as hyperuricemia control rats and not received any treatment. In contrast, the third, fourth, fifth, and sixth groups were treated daily with ginger extract, black seed extract, allopurinol (control positive), and a mixture of ginger + black seed extract, respectively. Results demonstrated that ginger administered orally to rats at a dose of 25 mg/kg was superior to the administration of black seed extract and a mixture of both of them, particularly in enhancing the percentage of spermatozoa normalization, normalization of serum sexual hormones (testosterone, luteinizing hormone (LH) and follicular stimulating (FSH)) level, as well as normalization of oxidative parameters (GPX, SOD, and CAT) and improving histopathological alterations. In conclusion, I realized that supplementation of ginger extract to hyperuricemia rats for two weeks was significantly (P < 0.05) normalized the majority of abnormalities in the male reproductive system induced by hyperuricemia.
Keywords: Natural plant metabolite; hyperuricemia; antioxidant enzymes; animal model; male reproductive system